TRANSPORT SÛR ET DURABLE : CONCEPTS, ETAT DES LIEUX AU MAROC ET PROPOSITION D’UNE REFLEXION INNOVANTE EN SYSTEME DE MANAGEMENT DE TRANSPORT SÛR ET DURABLE (TSD) (Partie 1 : l’assise scientifique ) - Kammas, M. Said; Zendal, M. Sohaib (European Scientific Journal, ESJ, 2014)
The transport sector is one of the strategic sectors of the economy in which the stakes are high.Transport in general, generates negative externalities widely recognized as well as denounced. In addition, aspects of security and sustainability have become sine qua non in almost all areas of public action. Therefore, security and sustainability have become a cornerstone in the policies of Transport via the concept of safe and sustainable transportation. This is especially with regard to road safety that the stakes of sustainability seem most important: the transport accident rate is indeed higher and higher and unbalanced modal share gets deeper, at the expense of other modes. The article will present a field to study the current state of the road safety in Morocco and a full presentation of the players involved for a safe and sustainable transport and finally come out with a new thinking on the optimal mode of governance, allowing control of the DOTS strategy in a participatory and responsible logic. Among the issues being studied on which this article is expected to make recommendations, may include:  The development and implementation of a Moroccan transport policy  The integration of actors from across the country in safety and transport sustainability,  Statistical analyzes of trends in traffic, road accidents of road safety in Morocco